Association between body mass index and clinical outcomes in out-of-hospital cardiac arrest survivors treated with targeted temperature management. Issue 5 (30th April 2021) - Chen, Chung-Ting; Lin, Meng-Chen; Lee, Yi-Jing; Li, Li-Hua; Chen, Ying-Ju; Chuanyi Hou, Peter; How, Chorng-Kuang
Abstract : Background: To determine the impact of body mass index (BMI) on clinical outcomes in out-of-hospital cardiac arrest (OHCA) survivors treated with targeted temperature management (TTM). Methods: We conducted a retrospective cohort study of 261 adult OHCA survivors who received complete TTM between January 2011 and December 2018 using data from the Research Patient Database Registry of Partners HealthCare system in Boston. Patients were categorized as underweight (BMI < 18.5 kg/m 2 ), normal weight (BMI = 18.5–24.9 kg/m 2 ), overweight (BMI = 25–29.9 kg/m 2 ), and obese (BMI ≥ 30 kg/m 2 ), according to the World Health Organization classification. Results: The average BMI was 28.9 ± 7.1 kg/m 2 . Patients with a higher BMI had higher rates of hypertension and diabetes mellitus, and were more likely to be witnessed on collapse. Patients with lower BMI levels had higher sequential organ failure assessment (SOFA) scores, blood urea nitrogen values, and mild thrombocytopenia rates (platelet count <150 K/μL) after the TTM treatment. The survival to discharge and favorable neurological outcome at discharge were reported in 117 (44.8%) and 76 (29.1%) patients, respectively. The survival at discharge, favorable neurologic outcomes at discharge, length of hospital admission, and the occurrence of acute kidney injury did not significantly differ between the BMI subgroups. In logistic regression model, BMI was not an independent predictor for survival at discharge (adjusted odds ratio 0.945, 95% CI 0.883–1.012, p = 0.108) nor for the favorable neurologic outcome at discharge (adjusted odds ratio 1.022, 95% CI 0.955–1.093, p = 0.528). Conclusion: In OHCA patients treated with TTM, there was no significant difference across BMI subgroups for survival or favorable neurologic outcome at discharge.